THE IMPORTANCE OF ARABIC LANGUAGE IN DA’WAH ACTIVITIES: A STUDY OF WOMEN IN DA’WAH - Atiku Garba Yahaya; Fatima Muhammad Sani (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
This paper is on the importance of Arabic language and its usage in Da’awah activities by women in Da’awah in Nigeria. It also discussed how Arabic is used in Da’awah by Muslim women in Nigeria. It explained the mission and vision of Women in Da’awah (WID) and their various approaches to Da’awah that includes encouragement of the use and study of Arabic language. Likewise, the paper discusses the Da’awah activities of the Women in Da’awah and outline most the da’awah activities carried out by the organization. It also deliberates the importance of the use of the language for Da’awah purpose with evidence from the Qur’an and Sunnah. The paper adopted and used descriptive approach combined with content analysis approach. Arabic is a compulsory language. When Islam stretched and came into contact with other civilizations, Arabic acted as a bridge of scholarship through the movement of translation. Makalah ini membahas tentang pentingnya bahasa Arab dan penggunaannya dalam kegiatan Dakwah oleh wanita dalam Dakwah di Nigeria. Dibahas pula bagaimana bahasa Arab digunakan dalam dakwah oleh wanita Muslim di Nigeria. Dijelaskan misi dan visi Women in Dakwah (WID) dan berbagai pendekatan mereka terhadap Dakwah yang mencakup dorongan penggunaan dan studi bahasa Arab. Demikian pula, makalah ini membahas kegiatan Dakwah para Wanita dalam Dakwah dan menguraikan sebagian besar kegiatan dakwah yang dilakukan oleh organisasi tersebut. Hal ini juga membahas pentingnya penggunaan bahasa untuk tujuan Dakwah dengan bukti dari Al-Qur'an dan Sunnah. Makalah ini mengadopsi dan menggunakan pendekatan deskriptif yang dikombinasikan dengan pendekatan analisis isi. Bahasa Arab adalah bahasa wajib. Ketika Islam merentang dan bersentuhan dengan peradaban lain, bahasa Arab berperan sebagai jembatan keilmuan melalui gerakan penerjemahan.